Enhancing Arabic Speaking Skills through Classroom Language: A Study at Darul Falah Institute Selangor Malaysia - Muhammad Bari’us Salam; Ahmad Maghfurin; Faruq Ihsan Nasrullah; Abdul Jalil Musthofa; Fahmi bin Masthur (Mantiqu Tayr: Journal of Arabic Language, 2025)
Institute Darul Falah Selangor has minimal practice of using Arabic in daily conversations due to the focus of Institute in memorizing the Qur'an is a factor in the lack of Arabic speaking skills here. Thus, the purpose of this studi is to discover the effectiveness of Classroom Language usage to the students’ speaking skills that are lacking because of it. It study this effectiveness both in students’ speaking skill inside the class and outside the class. This study used quantitative approach. The data collection methods used were observation, tests, and interviews. This study used pre-experimental type of study. Its sampling method is purposive sampling and had the students of upperclassmen as its’ samples. The data findings were analyzed using paired samples T-test on Microsoft excel. The result obtained was that the T score amounted to 5.840 > the T value at a significant level of 0.05 and can be concluded the significance of the impact of using Classroom Language on Arabic speaking skills. Moreover, the impact can also be seen in the increased intensity of Arabic usage in students' daily conversations. Thus, this study helps the development of an evidece-based framework for integrating classroom language strategies into Arabic language curricula and create replicable model for Arabic education studies. However, because this study focused solely on speaking skills within a limited timeframe, future research may explore the effects of classroom language on other skills over a more extended period.